Innovative water-saving ground cover rice production system increases yield with slight reduction in grain quality. (April 2020) - Guo, Lin; Liu, Meiju; Tao, Yueyue; Zhang, Yanan; Li, Guoyuan; Lin, Shan; Dittert, Klaus
Abstract: Ground cover rice production system (GCRPS) is known to increase grain yield and reduce irrigation water and greenhouse gas emission. However, whether this innovative technology affects commercial and nutritional rice quality remains unknown. Thus, a three-year field experiment was conducted to compare three production systems: traditional paddy (Paddy) and GCRPS under two soil moisture conditions, namely, saturated and 80% of soil water-holding capacity combined with three nitrogen fertilizer regimes. We analyzed the grain-milling quality (brown rice rate, milled rice rate and head rice recovery), the appearance quality (chalky rice rate and grain size), eating quality (amylose concentration) and nutritional quality (protein and 15 amino acids concentration). Results showed that compared with Paddy, the average rice grain yield, water and nitrogen use efficiency were significantly higher in GCRPS. The milling quality was improved in GCRPS, whereas the appearance quality decreased. Amylose concentration was 7.6% higher in saturated GCRPS than in Paddy. Moreover, protein concentration was 11.5%–13.1% lower in GCRPS than in Paddy and total amino acid concentration was reduced by 6.9%, whereas protein and total amino acid yield were significantly improved. Meanwhile, the concentrations of six essential amino acids were similar to those in Paddy, whereas non-essential amino acid concentration decreased in GCRPS. Overall, our findings showed that suitable N management practices for GCRPS are to be developed to further enhance the protein and amino acid concentrations. Highlights: Yield, water and nitrogen-use efficiency were higher in GCRPS than in Paddy. Milling quality was increased in GCRPS, appearance and eating qualities were reduced. Concentrations of protein and amino acid were lower in GCRPS, but yields were higher. Non-essential amino acid amount was lower in GCRPS, but essentials were unchanged.